Exploring the mediating role of meaning in life and psychological resilience in the relationship between physical exercise and sleep quality among Chinese secondary school students - Yao, Lihua; Wu, Yang; Guo, Kelei; Xiang, Jun (Frontiers in Psychology, 2025)
IntroductionThe persistent decline in adolescents’ sleep quality has become a significant public health issue affecting their physical and mental well-being as well as academic development, necessitating the exploration of effective intervention strategies.ObjectiveTo investigate the relationship between physical exercise and sleep quality among middle school students, and to examine the chain-mediated role of life meaning and psychological resilience in this relationship.MethodsA stratified cluster sampling method was employed to conduct a questionnaire survey among 1,579 junior high school students (833 males, 746 females). Measurement tools included the Revised Physical Exercise Scale, the Pittsburgh Sleep Quality Index, the Sense of Meaning in Life Scale, and the psychological resilience subscale from the Positive Adolescent Development Scale. Data analysis employed Pearson correlation analysis supplemented by bias-corrected percentile bootstrap methods.Results(1) Physical exercise showed a significant positive correlation with sleep quality (R = 0.268, p < 0.001), with a significant direct effect (β = 0.028, p < 0.001); (2) Physical exercise showed significant positive correlations with both life meaning (β = 0.517, p < 0.001) and psychological resilience (β = 0.132, p < 0.001). Life meaning was significantly positively correlated with psychological resilience (β = 0.120, p < 0.001) and sleep quality (β = 0.007, p < 0.001). Psychological resilience was significantly positively correlated with sleep quality (β = 0.079, p < 0.001); (3) Chain mediation analysis revealed that both life meaning and psychological resilience significantly mediated the relationship between physical exercise and sleep quality, involving three pathways: physical exercise → life meaning → sleep quality (mediation effect accounts for 10.35%), physical exercise → psychological resilience → sleep quality (mediation effect accounts for 34.48%), physical exercise → sense of meaning in life → psychological resilience → sleep quality (mediation effect accounts for 17.24%).ConclusionPhysical exercise not only directly improves sleep quality among secondary school students but also exerts indirect positive effects by enhancing sense of meaning in life and psychological resilience. This study provides empirical support for understanding the mechanism linking physical exercise, psychological resources, and sleep quality. Practically, schools and educational authorities can embed regular, diverse physical exercise programs into curricula and integrate activities fostering life meaning and psychological resilience to form a synergistic intervention mechanism, thereby promoting adolescent mental health and high-quality sleep. Policy makers can accordingly incorporate psychological adaptability and life meaning education into campus health promotion and youth sports development plans, providing comprehensive strategies to enhance adolescent sleep quality.